Relaps in Schizofhrenia Patient - Cucu Rokayah; Putri Mutiara Rima (Jurnal Ilmu Keperawatan Jiwa, 2020)
Schizophrenia is a psychotic disease that requires long-term treatment.  The disease has a remission period, but patients often return with positive symptoms, require emergency services and are called relapse.  This study aims to determine the factors that cause relapse or relapse in schizophrenia patients.  The type and method used in this research is descriptive.  The design of this study was Literature Review by analyzing 10 article from Goolgle Schoolar and Ebsco database, from 2011-2019, and then the analytical using naratif method to answer  about Relapse in Patients with Schizophrenia.  The results of this study stated that there are several factors that can trigger relapses in people with mental disorders, namely drug withdrawal and family support factors.  Therefore it can be concluded that to prevent relapse / recurrence in patients can be done with adherence to taking medication the patient must always be maintained so as to reduce the risk of patient recurrence.